Primary Cutaneous Anaplastic Large-Cell Lymphoma With 6p25.3 Rearrangement in a Cardiac Transplant Recipient: A Case Report and Review of the Literature. (June 2016) - Olson, Luke C.; Cheng, Esther; Mathew, Susan; Torres-Quinones, Marta; Magro, Cynthia
Abstract : Abstract: Posttransplant lymphoproliferative disorders define an important form of lymphoproliferative disease causally linked with a state of iatrogenic immune dysregulation inherent to the posttransplant setting. Most posttransplant lymphoproliferative disorders are in the context of Epstein–Barr virus–associated B-cell lymphoproliferative disease, most notably diffuse large-cell B-cell lymphoma. A less common variant falls under the rubric of posttransplant T-cell lymphoproliferative disease, which is largely unrelated to Epstein–Barr virus infection. Anaplastic large-cell lymphoma (ALCL) is the most recognized form of posttransplant T-cell lymphoproliferative disease. Although the 6p25.3 translocation is seen in a variety of B-cell lymphoproliferative disorders, this particular translocation in the spectrum of T-cell lymphoproliferative disease is a fairly specific finding pointing toward a diagnosis of primary cutaneous ALCL and a rare subset of lymphomatoid papulosis. This translocation in the peripheral T-cell lymphoma setting serves as a favorable prognostic predictor. We report a case of an 81-year-old heart transplant recipient who developed an expansile neck mass 17 years after his heart transplant. A diagnosis of cutaneous ALCL was subsequently made with cytogenetic analysis yielding the 6p25.3 translocation. The characteristic biphasic morphology of a small-cell epidermotropic neoplastic cell populace in concert with a dermal based large-cell infiltrate characteristic for those cases of ALCL harboring this translocation was seen. After excision of the nodule, his azathioprine was withheld. He is currently alive and well without evidence of disease.